Learning Obstacle Pada Materi Peluang Pada Siswa Kelas X SMAN 8 Palembang - Artadana, I Gede Gelgel; Destiniar, Destiniar; Fuadiah, Nyiayu Fahriza (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to identify the types of learning obstacles faced by class X students at SMA Negeri 8 Palembang in understanding the material on probability. The research method used is descriptive qualitative, with data collection through interviews, literature studies, field notes, video recordings of learning, and written tests. The data analysis process includes data reduction, data presentation, and drawing conclusions based on valid evidence. The results of the study indicate that students experience three types of learning obstacles in the material on probability: (1) Ontogenically obstacle, which includes lack of motivation, mental readiness, and adequate learning equipment; (2) Didactic obstacle, which is caused by teaching methods that are less varied and the selection of inappropriate teaching materials; and (3) Epistemological obstacle, which is related to limited understanding of the concept of probability material, where students have difficulty understanding and applying the concept as a whole. These findings emphasize the need to improve teaching methods and conceptual understanding to deal with learning obstacles experienced by students. This study is expected to provide recommendations for improving teaching for students, teachers, and schools in order to improve the quality of mathematics learning and encourage students’ interest and motivation in learning.